Recent Advances in Biopesticides: A Review of Efficacy and Environmental Impact - Shamsuddeen, Ruslan; Mathew, Twan Sale; Haladu, Mohammed; Ahmad, Kabiru Bashir; Adam, Ansar Bilyaminu; Abubakar, Musa Yahaya (Darul Yasin Al Sys, 2024)
Biopesticides are a vital component of sustainable agriculture, offering a safer alternative to synthetic pesticides. This review provides an overview of recent advances in biopesticides, including their types, efficacy, and environmental impact. Microbial, plant-based, and biochemical biopesticides have shown promising results in controlling pests and diseases. While efficacy is comparable to synthetic pesticides, biopesticides have a more favorable environmental profile, with reduced toxicity to non-target organisms and biodegradability. However, challenges persist in registration, regulation, and public acceptance. Future directions include genetic engineering, nanotechnology, and integrated pest management strategies. This review highlights the potential of biopesticides in reducing the environmental footprint of agriculture and ensuring food security.